Descriptίοn of Aceria creticα new species from olive trees in Greece (Acari: Εriophyidae) - Hatzinikolis, Ε. Ν. (ENTOMOLOGIA HELLENICA, 1989)
The female of Aceria cretica, new species, is described and illustrated. This species was found and collected from an isolated group of olive trees (Olea europaea L.) in Crete, Greece. It causes subcircular, greenish patches under leaf surface, similar to those caused by Aceria oleae (Nalepa 1900).